2010
DOI: 10.1634/theoncologist.2010-0020
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Oral Lactoferrin Supplementation in Combination with rHuEPO-β for the Treatment of Anemia in Advanced Cancer Patients Undergoing Chemotherapy: Open-Label, Randomized Controlled Study

Abstract: Advanced-stage cancer patients often suffer from anemia that closely resembles the anemia of chronic inflammatory diseases characterized by specific changes in iron homeostasis and absorption. i.v. iron improves the efficacy of recombinant human erythropoietin (rHuEPO) in anemic cancer patients undergoing chemotherapy. We report the results of an open-label, randomized, prospective trial aimed at testing the efficacy and safety of treatment with oral lactoferrin versus i.v. iron, both combined with rHuEPO, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 36 publications
2
70
0
3
Order By: Relevance
“…It has been reported that hLF treatment can decrease the serum CRP levels in many systemic diseases (30). The present study documents the decrease of splenic and hepatic immune responses and iNOS and MPO expression.…”
Section: Discussionsupporting
confidence: 80%
“…It has been reported that hLF treatment can decrease the serum CRP levels in many systemic diseases (30). The present study documents the decrease of splenic and hepatic immune responses and iNOS and MPO expression.…”
Section: Discussionsupporting
confidence: 80%
“…The present findings suggest that a careful evaluation of cancer patients should be performed before starting treatment for anemia: in addition to including erythropoiesis-stimulating agents, the treatment of CRA should include the correction of nutritional deficiencies, personalized iron supplementation 42,43,51 and, in some cases, antioxidant treatment. 52 Moreover, our results suggest that patients with different cancer types and at various stages may have different factors influencing the pathogenesis and severity of anemia and, therefore, need specific individualized mechanism-based treatment of CRA.…”
Section: Discussionmentioning
confidence: 94%
“…iron. 43 Cancer growth and associated inflammation also induce changes in energy metabolism and food intake (canceranorexia), potentially contributing to anemia. These conditions lead to severely altered glycemia, albumin, and cholesterol levels, with consequent reduced circulating leptin levels.…”
Section: Discussionmentioning
confidence: 99%
“…This significant improvement is contrary to that observed in Maccio et al, (2010) study where cancer patients with anemia of chronic disease were administered lactoferrin along with erythropoietin. 24 Hence, the beneficial effect of lactoferrin, seen in cases of nutritional ID, does not extrapolate to anemia of chronic disease. Since there was no statistically significant difference in the iron parameters and Hb levels in post therapy compared to baseline, it can be quoted that there are no hematological benefits of combining OFS with OLFBC.…”
Section: Resultsmentioning
confidence: 99%